Impact of digital transformation on security policies and standards (A volume in the Advances information security, privacy, and ethics (AISPE) book series, 2020)
"This book summarizes the policies, standards, and mechanisms for security in all sort of digital applications. It also focuses on blockchain and its imminent impact on financial services in making a smart government along with bitcoin and the future of digital payments"